2004
DOI: 10.1093/ps/83.4.662
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of endo-β-D-mannanase (Hemicell) effects on broiler performance and energy use in diets varying in β-mannan content

Abstract: Two experiments were conducted to evaluate the effects of a commercial endo-beta-D-mannanase (Hemicell) on overall performance, MEn, net energy for gain, and some serum parameters of broilers fed diets varying in beta-mannan level (experiment 1) and to evaluate effects of enzyme level on the same variables in broilers fed diet high in beta-mannan (experiment 2). As a semipurified beta-mannan source, guar gum was used to alter the dietary beta-mannan level. In experiment 1, guar gum was added at 0, 0.5, 1, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 2 publications
7
73
0
1
Order By: Relevance
“…The untreated GRM used in the present study had 10.99% of guar gum and its quantity did not significantly reduce even after fungal fermentation (10.17%). Daskiran et al (2004) reported that the usage of fibrolytic enzymes alleviated the deleterious effect of guar gum by increasing intestinal viscosity of animals. A. niger would have produced these enzymes during fermentation as earlier reported by Solis-Pereyra et al (1996), Maciel et al (2008) and Reddy et al (2015).…”
Section: Resultsmentioning
confidence: 99%
“…The untreated GRM used in the present study had 10.99% of guar gum and its quantity did not significantly reduce even after fungal fermentation (10.17%). Daskiran et al (2004) reported that the usage of fibrolytic enzymes alleviated the deleterious effect of guar gum by increasing intestinal viscosity of animals. A. niger would have produced these enzymes during fermentation as earlier reported by Solis-Pereyra et al (1996), Maciel et al (2008) and Reddy et al (2015).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas Jackson et al (2003Jackson et al ( , 2004 and Daskiran et al (2004) reported beneficial effects on BWG and FCR during starter and grower phases of growth from 80 or 110 unit/g β-mannanase supplementation. Similarly, Kidd et al (2001) fed broilers corn and soybean meal based diets with or without anα-galactosidase (112 g/ton) enzyme.…”
Section: Discussionmentioning
confidence: 96%
“…Lee et al (2005) reported that Hemicell significantly reduced the FCR of guar germ diets to a level comparable with the positive and negative control diets. Daskiran et al (2004) added Hemicell at 0.5, 1 and 1.5% in a corn-soybased starter diet containing 1% GM and found that Hemicell improved FCR at all inclusion levels.…”
Section: Discussionmentioning
confidence: 99%